Overcoming Financial Challenges for Small and Medium Enterprises: Strategies for Entrepreneurial Success - Karikari Amoa-Gyarteng (ZBW – Leibniz Information Centre for Economics, 2023)
The article discusses the challenges faced by small and medium-sized enterprises (SMEs) in obtaining finance, which is a critical issue for their growth and profitability. It highlights that SMEs often lack collateral and financial history, which makes it difficult for them to obtain loans from traditional financial institutions. The article then explores two approaches to entrepreneurship, Effectuation and Bricolage, which focus on internal resourcefulness and making the most of what is available, regardless of long-term returns. The paper lists ten strategies that entrepreneurs can adopt including embracing affordability logic, engaging in networking and collaboration among others. By implementing these strategies, SMEs can overcome funding challenges and achieve sustainable growth.
Keywords: 330; Effectuation; Bricolage; SMEs; Financial Challenges; Strategies